EDUKASI KESEHATAN PADA IBU HAMIL PADA MASA PANDEMI COVID-19 DI RW III KELURAHAN PAMPANGAN NAN XX KOTA PADANG - Desmawati Desmawati; Ulvi Mariati; Miranie Safaringga; Fitri Khoiriyah; Yessi Pertiwi; Annisa Defani; Rena Afri Ningsih; Fonny Kurnia Putri; Ilvira Ulpa Ismail; Nadya Khaira Nurdi; Yusrawati Yusrawati; Aldina Ayunda Insani; Vaulinne Basyir; Hudila Rifa Karmila (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2021)
The class for pregnant women is a place to increase knowledge, attitudes, and behavior of mothers during pregnancy. Currently the world is facing the Covid-19 pandemic caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The current condition of the Covid-19 pandemic has caused the mother's class activities to not be carried out properly. Health services must continue to run optimally, safe for patients, health workers including midwives. This activity aims to create a complete understanding in all sectors regarding maternal and child health services with preventive and promotive efforts through organizing, community empowerment and empowering women in the community. The method used is a mixed method, descriptive qualitative and quantitative by means of in-depth interviews and surveys conducted boldly (WA Group for pregnant women, and Via Phone, Video Call/SMS). The results of 6 pregnant women in RW III, it was found that 100% of pregnant women had never attended classes for pregnant women during the Covid-19 pandemic, and 100% of pregnant women were worried about pregnancy during the Covid-19 pandemic. Interventions were carried out in the form of advocacy to the puskesmas and midwives of supporting health centers, as well as empowering health cadres in carrying out classes for pregnant women by utilizing online technology via WhatsApp groups, Zoom Meetings, Video Calls and the Tiktok application. It is hoped that cadres will play an active role and collaborate with midwives and health workers in terms of providing health information, especially those related to the health of pregnant women by utilizing online media, so that the health of pregnant women is monitored during the COVID-19 pandemic.